Morphological identification of crabs in the rocky coast of Manado Bay - Rustikasari, Irna; Paransa, Darus S. J.; Kaligis, Erly Y.; Ompi, Medy; Pelle, Wilmy E.; Pratasik, Silvester B. (Sam Ratulangi University, 2021)
Coastal areas have a wealth of biological natural resources including marine life such as crustaceans. One of the marine organisms in the crustacean group is the crab. The purpose of this study was to identify the types of crabs that live in rocky coastal habitats through a morphological approach. To determine the morphology of crabs can be done by looking at the shape, color, and size. The results of this study found 3 types of crabs in two locations in the Manado Bay area including the crab is Grapsus albolineatus, Ozius truncatus, and Uca (Galasimus) tetragonon. Based on the results of the research above, morphological forms were found on the abdomen in the form of a tapered triangle which indicated that the crab was male and the abdomen was triangular with the female sex. The most common crabs found at the study site were female crabs.Keywords: Coastal Area; Crab; MorphologyÂ AbstrakWilayah pesisir memiliki kekayaan sumber daya alam hayati diantaranya biota laut seperti krustasea. Salah satu organisme laut dalam golongan krustasea adalah kepiting. Tujuan dari penelitian ini adalah untuk mengidentifikasi jenis kepiting yang hidup di habitat pantai pesisir berbatu melalui pendekatan morfologi. Untuk mengetahui morfologi pada kepiting dapat dilakukan dengan melihat bentuk, warna serta ukuran. Hasil penelitian ini menemukan 3 jenis spesies kepiting pada dua lokasi yang berada di daerah Teluk Manado diantaranya kepiting Grapsus albolineatus Ozius truncatus dan Uca (Galasimus) tetragonon. Berdasarkan hasil penelitian diatas maka ditemukan bentuk morfologis pada bagian abdomen berbentuk segitiga meruncing yang menunjukkan bahwa kepiting tersebut berkelamin jantan dan abdomen berbentuk segitiga melebar merupakan kepiting dengan jenis kelamin betina. Kepiting yang paling banyak ditemukan pada lokasi penelitian adalah kepiting betina. Â Kata Kunci: Wilayah Pesisir; Kepiting; MorfologiÂ